2000
DOI: 10.1006/viro.2000.0277
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of HIV-1 Nef with the μ Subunits of Adaptor Protein Complexes 1, 2, and 3: Role of the Dileucine-Based Sorting Motif

Abstract: HIV-1 Nef interacts with cellular adaptor protein (AP) complexes and their medium (mu) subunits. However, the role of the dileucine-based sorting motif within Nef in these interactions has been incompletely characterized. Here, yeast two-hybrid assays indicated that HIV-1 Nef interacted not only with the mu subunits of AP-1 and AP-2, but also with that of AP-3. The interactions with mu1 and mu3 were markedly stronger than the interaction with mu2. Leucine residues of the sorting motif were required for the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 44 publications
3
94
1
3
Order By: Relevance
“…Nef, in contrast, is expressed immediately following infection and stimulates the internalization and degradation of CD4 molecules already present on the surface of the infected cell prior to Env and Vpu expression (2,12,59). Nef interacts simultaneously with the cytoplasmic tail of CD4 and members of the cellular clathrin endocytic machinery, such as adaptor proteins (9,19,27,30,41), ␤-cop (5,56), and/or vacuolar ATPase (42,44). Nef thus directs infected cell surface CD4 to cellular endocytic pathways and to its subsequent degradation in lysosomes.…”
mentioning
confidence: 99%
“…Nef, in contrast, is expressed immediately following infection and stimulates the internalization and degradation of CD4 molecules already present on the surface of the infected cell prior to Env and Vpu expression (2,12,59). Nef interacts simultaneously with the cytoplasmic tail of CD4 and members of the cellular clathrin endocytic machinery, such as adaptor proteins (9,19,27,30,41), ␤-cop (5,56), and/or vacuolar ATPase (42,44). Nef thus directs infected cell surface CD4 to cellular endocytic pathways and to its subsequent degradation in lysosomes.…”
mentioning
confidence: 99%
“…Of note, Nef-GFP appears as effective as wild-type Nef for all its functions studied to date (35,36). To label the lipid rafts, which are enriched with the ganglioside GM1, a sphingolipid specifically recognized by CT-B, we incubated the cells with recombinant CT-B conjugated to Alexa Fluo 594.…”
Section: Nef Is Recruited Into the Is After Tcr Engagementmentioning
confidence: 99%
“…For example, interactions between Nef and b-Cop target CD4 to late acidic endosomes whereas interactions with AP-2 target CD4 to clathrin-coated pits (early endosomes). [32][33][34] Studies have shown that Nef expression leads to changes within the endosomal compartment and increases endosome, lysosome, and late endosome/multivesicular body (MVB) production in hematopoietic cells. [35][36][37] MVBs contain smaller membrane-bound vesicles that fuse with plasma membranes and are released via exocytosis into the extracellular space as exosomes ranging in size from 30 to 200 nm in diameter.…”
Section: Introductionmentioning
confidence: 99%